2016
DOI: 10.1002/2016gl067949
|View full text |Cite
|
Sign up to set email alerts
|

El Niño–Southern Oscillation influence on tropospheric mercury concentrations

Abstract: The El Niño–Southern Oscillation (ENSO) affects the tropospheric concentrations of many trace gases. Here we investigate the ENSO influence on mercury concentrations measured in the upper troposphere during Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrumented Container flights and at ground at Cape Point, South Africa, and Mace Head, Ireland. Mercury concentrations cross‐correlate with Southern Oscillation Index (SOI) with a lag of 8 ± 2 months. Highest mercury concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Meehl and Arblaster (2001) also report that TBOs with roughly a 2-3-year period encompass most ENSO years with their well-known biennial tendency. Slemr et al (2016) analyzed mercury data from Cape Point in South Africa, Mace Head in Ireland, and CARIBIC measurements in the upper troposphere and found an ENSO signature in all these data sets. Thus the finding of biennial variation of GEM concentrations at Cape Point is consistent with the ENSO influence.…”
Section: Resultsmentioning
confidence: 99%
“…Meehl and Arblaster (2001) also report that TBOs with roughly a 2-3-year period encompass most ENSO years with their well-known biennial tendency. Slemr et al (2016) analyzed mercury data from Cape Point in South Africa, Mace Head in Ireland, and CARIBIC measurements in the upper troposphere and found an ENSO signature in all these data sets. Thus the finding of biennial variation of GEM concentrations at Cape Point is consistent with the ENSO influence.…”
Section: Resultsmentioning
confidence: 99%
“…Slemr et al [] suggested that the variation in Hg concentrations may be linked to increased biomass burning during years with a strongly negative Southern Oscillation Index (El Niño). Using CO data from MLO, three IMFs for CO have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite was found to be true for O 3 (see Figure 6); hence, lower Hg concentrations are associated with O 3 -rich FT air. Slemr et al [2016] suggested that the variation in Hg concentrations may be linked to increased biomass burning during years with a strongly negative Southern Oscillation Index (El Niño). Using CO data from MLO, three IMFs for CO have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Tropospheric mercury concentrations were found to be influenced by El Niño Southern Oscillation (ENSO) (Slemr et al, 2016b). Such influence could also be a reason for the observed inter-annual variation of GEM concentrations at Cape Point.…”
Section: Inter-annual Variations Of Gem Concentrationsmentioning
confidence: 99%